Voltammetric monitoring of photochemical reactions: Photo-induced electron transfer to p-chloronitrobenzene - Kumbhat, S; Webster, R; Marken, F; Eklund, J; Compton, R (1996)
Channel electrode voltammetry using an irradiated gold electrode is used to study the photolysis of p-chloronitrobenzene in aqueous ethanolic solution in the presence of the hydroxide anion. The formation of the stable radical anion, [p-ClC6H4NO2]•-, via light-induced electron transfer is demonstrated and kinetic parameters are reported.